Role of FlgM in sigma D-dependent gene expression in Bacillus subtilis. - Caramori, T (1996)
The alternative sigma factor sigma D directs transcription of a number of genes involved in chemotaxis, motility, and autolysis in Bacillus subtilis (sigmaD regulon). The activity of SigD is probably in contrast to that of FlgM, which acts as an antisigma factor and is responsible for the coupling of late flagellar gene expression to the assembly of the hook-basal body complex. We have characterized the effects of an in-frame deletion mutation of flgM. By transcriptional fusions to lacZ, we have shown that in FlgM-depleted strains there is a 10-fold increase in transcription from three different sigmaD-dependent promoters, i.e., Phag, PmotAB, and PfliDST. The number of flagellar filaments was only slightly increased by the flgM mutation. Overexpression of FlgM from a multicopy plasmid under control of the isopropyl-beta-D-thiogalactopyranoside-inducible spac promoter drastically reduced the level of transcription from the hag promoter. On the basis of these results, we conclude that, as in Salmonella typhimurium, FlgM inhibits the activity of SigD, but an additional element is involved in determining the number of flagellar filaments.